The Origin, Development and Decline of Back-to-Back Houses in Leeds, 1787–1937. (3rd July 2017) - Harrison, Joanne
Abstract : This paper traces the development of back-to-back house building in Leeds. It first outlines the origin of the house type, before examining the urban layout, building form and social aspects of back-to-back courts in the first half of the 19th century, and the role of speculative developers, building societies and sanitary reformers. The focus then turns to the bills, acts and by-laws of the later 19th and early 20th century, and the determination of the people of Leeds to retain their preferred house type. Together, these brought improvements to the design and facilities, culminating in a house type that was far superior to that which was condemned by the back-to-back critics, and arguably had overcome all of the criticisms by the time construction of back-to-backs was prohibited in 1909.